Improved Gardner Symbol Timing Recovery based on Digital Control Theory - Alobaidi, Saadi A. (International Journal of Engineering and Technology, 2018)
The study and investigation of Gardener timing error detection performance over Quadrature phase shift keying (QPSK) modulator based on digital control theory is presented in this paper. The stability demonstration of the following performance in any design by open loop techniques and normalizing timing error detection has been examined in MATLAB environments. The recovery of time symbol in second order loop transfer functions has capability to track the down phase with frequency offset situations. The performance of modulation scheme was observed to get lower bit error rate (BER). The proposed algorithms introduced a new technique to provide fewer samples per symbol and less complication due to collaboration with Fourier Transform in coherent receiver and elimination of multiplications. The Gardener timing recovery could operate in 2 samples in the symbol arrangements to enable the minimum receiver complexity. The simulation results shows that the inherent time jitter is outperforms the Gardener algorithms for low roll off factors and despite the reduction of complexity compared with existing techniques.